Giant aneurysm in a left coronary artery fistula: diagnostic cardiovascular imaging and treatment considerations. (8th May 2013) - Frestad, Daria; Helqvist, Steffen; Helvind, Morten; Kofoed, Klaus
Abstract : Congenital coronary artery fistula complicated with giant coronary artery aneurysm is a very rare condition. In this case report, we present a 65-year-old woman, referred to us with a continuous heart murmur, occasional atypical chest pain and few episodes of fainting. A giant aneurysm and a coronary–pulmonary fistula were diagnosed using multiple cardiovascular imaging modalities to provide a sufficient anatomical picture. The patient was considered at high risk of sudden death from aneurysm rupture and received surgical treatment. Subsequent histopathological examination revealed a true aneurysm with severe wall calcifications, ulcerations and large areas with marked thinning of the wall. The postoperative course was uneventful.